Effect of Rotation on Peristaltic Flow of Sutterby Fluid through a Wave Channel - Moean, Fatima Khalid; Al-Khafajy, Dheia G. Salih (Iraqi Journal of Science, 2025)
This study intends to investigate the effect of rotation on the peristaltic transport of non-Newtonian Sutterby fluid through wave channel. The equations are non-homogeneous and non-linear partial differential equations. The equations have been resolved using approximation long wavelength assumptions. The results have been examined through graphics using the “Mathematica 13” program. Therefore, it has been noticed that the effect of the flow rate, amplitude ratio, density of the fluid, viscosity of the fluid, rotation and tube's average radius on the distribution of velocity, pressure gradient, pressure rise, friction forces and stream function. It has been noticed by increasing the flow rate, amplitude ratio, density of the fluid and Sutterby fluid parameter, the velocity of fluid increases, but the fluid’s velocity decreases while the viscosity of the fluid increases.